2023
DOI: 10.3390/ijgi12070286
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-Based Evacuation Route Planning in Flood-Susceptible Area of Siraha Municipality, Nepal

Abstract: Flood is one of the most frequently occurring and devastating disasters in Nepal. Several locations in Nepal are at high risk of flood, which requires proper guidance on early warning and safe evacuation of people to emergency locations through optimal routes to minimize fatalities. However, the information is limited to flood hazard mapping only. This study provides a comprehensive flood susceptibility and evacuation route mapping in the Siraha Municipality of Nepal where a lot of flood events have occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
5
0
3
Order By: Relevance
“…Flood susceptibility risk maps prepared using geographic information systems and multi-criteria analysis have been shown to closely resemble historical flood ranges [49]. These maps are crucial for determining evacuation routes in highly flood-prone areas [50]. Additionally, flood risk maps have been utilized to identify hotspots that are highly susceptible to flooding and potential sources of pollutant contaminants [51].…”
Section: Influence Of Climate Seasonality and Floodsmentioning
confidence: 99%
“…Flood susceptibility risk maps prepared using geographic information systems and multi-criteria analysis have been shown to closely resemble historical flood ranges [49]. These maps are crucial for determining evacuation routes in highly flood-prone areas [50]. Additionally, flood risk maps have been utilized to identify hotspots that are highly susceptible to flooding and potential sources of pollutant contaminants [51].…”
Section: Influence Of Climate Seasonality and Floodsmentioning
confidence: 99%
“…The exercise of travelling by car has a dynamic speed depending on the speed limits of the localities. The service area shows the road networks that can be reached within different times, in minutes from the assembly points, and have been applied in evacuation route planning in disaster-susceptible areas (disasters such as floods and tsunamis) [52,53]. These outputs were then cross-referenced with the urban-forest interfaces of the two municipalities to find the travel times between these contact areas and the refuges and shelters.…”
Section: Spatial Variability In Wildfire Hazardsmentioning
confidence: 99%
“…On the other hand, GIS-based route planning has also attracted much attention [8,9,[14][15][16][17][18][19][20]. Ak and Bozkaya [8] utilized ArcMap to apply different route planning models and to visualize the hazmat transportation routes on the map.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis results indicated that the optimal transportation routes are different for the shortest path and the least vulnerable analyses. Other research groups [17][18][19][20] investigated GIS-based evacuation route planning during disasters, which is not the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%